Thoughts by her soul bookmark / Nur Anis Liyana Mat Aris … [et al.] - Mat Aris, Nur Anis Liyana; Mohd Zain, Zainab; Misman, Juritah; Abdul Hamid, Shareenie Shera (Academy of Language Studies, 2023)
The creative writing industry has many branches regardless of what language it is written in, including poetry, short stories, novels, memoir, and others. This project aims to help the public through self-expression and uncover the language influence in purchasing an item among the general society. Therefore, this study provides motivational encouragement for book readers through the creation of creative writing-based bookmarks featuring thoughts and quotes for "Thoughts by Her Soul". Besides selling it in bookmark form, it has been posted the thoughts and quotes on the project's Instagram account for the public to read. Moreover, the account is also used to promote the bookmark. This project has conducted an online survey to collect quantitative data and to identify opinions of the public in several areas. The findings revealed that language has influenced the decision of the society to purchase the bookmark.